Understanding the Greek Revolution (1821-1832) : New Approaches in Social, Political and Cultural History - Kolovos, Elias,; Kousouris, Dimitris, (Historical Materialism Book Series ;, 2024)
A part of the insurrectionary wave of the 1820s, the Greek Revolution remains a neglected episode in the revolutionary history of the period. The contributions included in this volume present the most recent research concerning the social, polit